The Impact of Marketing Mix Variables upon The Repurchase Intention of Customers in Mixue Tangerang City, Indonesia - Tarigan, Joshua Michael Servilo; Sibarani, Mentiana; Silitonga, Roland Y. H. (The Indonesian Institute of Science and Technology Research, 2024)
The franchise industry is one of the most prominent businesses in 2024, where Mixue is one of such brands that dominate the F&B franchise sector in the Indonesian market. Although Mixue shows high performance in Indonesia, there are a few exceptions in several regions where some outlets have declined such as Tangerang City, Indonesia. Hence research is needed to see the viewpoint of Mixue Tangerang City's citizens on the marketing mix of Mixue, where the factors are as follows: Product, Price, Place, and Promotion. The evaluation is important to help owners adjust their marketing strategy specifically in Tangerang City to help boost citizen's intention to buy Mixue products again in the future (repurchase intention). The research is conducted qualitatively, where the samples used are the customers of Mixue Tangerang who have bought more than once. The response is collected using an online questionnaire, in which they answer using the Likert Scale. The result will be analyzed using the Multiple Linear Regression Analysis method using the software SPSS version 26. The research gains 103 Mixue Tangerang City customer respondents. The research shows that the variables of Product, Price, Place, and Promotion have a significant impact on Repurchase Intention simultaneously. Aside from that, the result shows that Product, Place, and Promotion each have a significant partial impact on Repurchase Intention. However, research shows that the Price factor does not have a significant partial impact on Repurchase Intention.